2013
DOI: 10.1186/1477-7525-11-218
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal quality of life analysis in a phenylketonuria cohort provided sapropterin dihydrochloride

Abstract: BackgroundSapropterin dihydrochloride effectively lowers plasma phenylalanine (Phe) for at least a third of phenylketonuria (PKU) patients, with potential for increased dietary Phe tolerance and decreased medical food requirement.ObjectiveTo investigate long-term quality of life (QOL) in patients with phenylketonuria (PKU) who took sapropterin (BH4, Kuvan®) for up to one year.Methods37 PKU patients, ages 10–49 years, were asked to complete a PKU-specific self-report QOL questionnaire (QOLQ) at baseline, 1, 4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 28 publications
3
25
1
1
Order By: Relevance
“…This striking difference between our findings and those of the studies from high-income countries could be attributed, in the case of the European multicenter study ( 28 ), to the access to pharmacological treatment with BH4, as increased Phe tolerance and reduced metabolic formula requirement in BH4-responsive patients can improve HRQoL ( 32 ). Nevertheless, this cannot be sustained as the other four studies were conducted before BH4 became available.…”
Section: Discussioncontrasting
confidence: 95%
“…This striking difference between our findings and those of the studies from high-income countries could be attributed, in the case of the European multicenter study ( 28 ), to the access to pharmacological treatment with BH4, as increased Phe tolerance and reduced metabolic formula requirement in BH4-responsive patients can improve HRQoL ( 32 ). Nevertheless, this cannot be sustained as the other four studies were conducted before BH4 became available.…”
Section: Discussioncontrasting
confidence: 95%
“…This provides a strong advantage over generic HRQoL measures [ 19 , 25 , 26 ], questionnaires developed for unspecific chronic illness (e.g. Ulm Quality-of-Life Inventory for Parents of chronically ill children) [ 22 ] or even the more recent “PKU-specific” HRQoL questionnaire (PKU-QOLQ) [ 21 ], which had been adapted from a questionnaire used in another condition (juvenile diabetes) and thus had not been designed fully from the beginning for patients with PKU specifically. Because it is truly disease specific, the PKU-QOL questionnaire captures aspects that are important for PKU patients and their parents and impact their daily lives (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…HRQoL studies focusing on patients with PKU and their parents are still scarce [ 18 - 22 , 11 , 23 - 27 ]. Most studies suggest that the HRQoL of patients with PKU is comparable to that of the general population [ 18 , 19 , 21 , 11 , 23 , 24 , 26 ] with the exception of a lower HRQoL demonstrated in a group of Italian children [ 20 ], a low score on the cognitive domain in adults [ 28 ], and of severe to moderate distress in 45% of non-compliant adults patients [ 18 ]. Parents of children with PKU perceive their HRQoL positively overall even though it may be affected by the emotional and social impact of parenting a child with PKU [ 22 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…These unexpected normal scores in most studies may result from the insufficient sensitivity of the presently available generic HRQoL measurement tools in detecting the specific problems of patients with PKU. This is confirmed by the fact that only a study using a partially validated PKU-specific questionnaire demonstrated an improvement in patients’ HRQoL after the start of BH 4 , which allowed relaxation of the diet in some of the patients [ 22 , 23 ]. Of note, in these studies, HRQoL was assessed for about 50 patients (maximum being 69 in Demirdas et al), always from one single country.…”
Section: Introductionmentioning
confidence: 94%